2002
DOI: 10.1074/jbc.m207294200
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin2 Is Critically Involved in CXCR4-mediated Chemotaxis, and This Is Mediated by Its Enhancement of p38 MAPK Activation

Abstract: Chemotaxis mediated by chemokine receptors such as CXCR4 plays a key role in lymphocyte homing and hematopoiesis as well as in breast cancer metastasis. We have demonstrated previously that ␤-arrestin2 functions to attenuate CXCR4-mediated G protein activation and to enhance CXCR4 internalization. Here we show further that the expression of ␤-arrestin2 in both HeLa and human embryonic kidney 293 cells significantly enhances the chemotactic efficacy of stromal cell-derived factor 1␣, the specific agonist of CXC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
295
1
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 338 publications
(313 citation statements)
references
References 39 publications
(30 reference statements)
12
295
1
2
Order By: Relevance
“…Indeed, several reports have shown that SAPK2/p38 is involved in chemokine-induced chemotaxis of cells (16,34,70,71). Our study also presents evidence that SAPK2/p38 and SAPK1/JNK1, but not ERKs, intervene in the control of MCP-1-induced MonoMac6 migration.…”
Section: Discussionsupporting
confidence: 68%
“…Indeed, several reports have shown that SAPK2/p38 is involved in chemokine-induced chemotaxis of cells (16,34,70,71). Our study also presents evidence that SAPK2/p38 and SAPK1/JNK1, but not ERKs, intervene in the control of MCP-1-induced MonoMac6 migration.…”
Section: Discussionsupporting
confidence: 68%
“…For example, β-arrestin-2-dependent stabilization of cytosolic IκBα and inhibition of NF-κB activation following LPS stimulation are essential for rapid and sufficient production of NO in response to microbial attack [14] . Moreover, there is accumulating evidence that β-arrestin-2, which is expressed abundantly in the spleen, is functionally involved in some important immune responses, such as regulation of lymphocyte chemotaxis and homing [24,25] . In the present study we used RNA interference against β-arrestin-2 to test its role in anti-inflammatory effects stimulated by β 2 -AR.…”
Section: Wwwchinapharcom Wang W Et Almentioning
confidence: 99%
“…The RNAi plasmid for human c-Src was constructed as described [31]. A 22-mer oligonucleotide (oligo1) corresponding to nucleotide 594-615 of the c-Src coding sequence was first inserted into the pBS/U6 vector (a generous gift from Dr Yang Shi, Dept.…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…Stable expression clones were selected and maintained in G418 (300 mg/ml). For transient transfection, HEK293 cells were transfected by the calcium phosphate-DNA co-precipitation method as described previously [31].…”
Section: Cell Culture and Transfectionmentioning
confidence: 99%